Prying Action for Slip-Critical Connections with Bolt Tension and Shear Interaction - Thornton, William A.; Muir, Larry S. (Engineering Journal, 2012)
When bolted connections subjected to both shear and tension must be checked for prying action, the interaction between tension and shear must be considered. The 2010 AISC Specification for Structural Steel Buildings (AISC 360-10) presents interaction equations both for bearing connections and for slip-critical connections. This paper demonstrates how these interaction equations may be used when applying the prying action analysis presented in the 14th edition Steel Construction Manual.